Preparation method of PVDF composite ultrafiltration membrane with underwater piezoelectric activity

By mixing graphene oxide into the casting solution of the PVDF piezoelectric material, and applying a negative DC electric field during the phase transformation process, combined with the hydrophobic modification technology, the problem of the low-voltage electrical output performance of the PVDF piezoelectric material under water is solved, achieving Significant improvement in underwater piezoelectric activity and electrostatic anti-pollution capabilities.

CN119327290AActive Publication Date: 2025-01-21TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202411610048.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

When using PVDF piezoelectric materials to control underwater membrane pollution, the prior art faces the problems of low-voltage electrical output performance and difficult to improve underwater performance expression.

Method used

By mixing the oxygen oxygenne in the casting liquid, and applying a negative polar DC electric field during phase conversion, combined with hydrophobic modification technology, it enhances the voltage electrical activity and underwater output performance of the PVDF composite ultrafiltration film.

Benefits of technology

It significantly improves the underwater voltage activity and electric anti -pollution capacity of the PVDF composite ultrafiltration membrane, and realize the excellent voltage performance expression.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327290A_ABST
    Figure CN119327290A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PVDF composite ultrafiltration membrane with underwater piezoelectric activity, and belongs to the technical field of water treatment. The preparation method of the PVDF composite ultrafiltration membrane with underwater piezoelectric activity comprises the following steps: dispersing graphene oxide in an organic solvent, then adding a pore-foaming agent and PVDF, heating and stirring until complete dissolution, and defoaming to obtain a membrane casting solution; a flat plate is coated with the membrane casting solution and then immersed in a pure water coagulating bath arranged in a negative electrode direct-current electric field for phase separation and synchronous polarization, and a PVDF porous membrane is obtained; and carrying out hydrophobic modification on the PVDF porous membrane to obtain the PVDF composite ultrafiltration membrane. GO is introduced in the PVDF separation membrane forming process, the negative electrode electric field polarization effect is synchronously applied, and then a hydrophobic modification method is combined, so that the PVDF composite ultrafiltration membrane with remarkable underwater piezoelectric activity and anti-pollution capacity is finally prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity. Background Art

[0002] In recent years, ultrafiltration technology has attracted widespread attention in water purification and comprehensive utilization of water resources due to its excellent removal performance for colloidal particles and pathogenic microorganisms. However, the pollution problems faced by ultrafiltration membranes in actual applications have restricted the further improvement of process efficiency. In response to the problem of ultrafiltration membrane pollution, electric field-assisted membrane pollution control technology has shown unique advantages in reducing chemical agent consumption, improving membrane separation efficiency, and slowing down membrane flux attenuation. However, traditional electric-assisted membrane pollution technology usually relies on external power supply, which aggravates energy consumption and is difficult to meet the development requirements of green and low-carbon membrane separation technology. In response to this problem, new membrane pollution control technologies based on the intrinsic piezoelectric properties of membrane materials have gradually become feasible alternatives. Especially for polyvinylidene fluoride (PVDF) ultrafiltration membranes, PVDF is not only one of the most widely used membrane-making polymers, but also a typical organic piezoelectric material (β-phase PVDF). Different from traditional conductive membrane or electric field assisted membrane pollution control technology, PVDF piezoelectric separation membrane can directly convert the redundant mechanical energy in the pressure-driven membrane separation process into membrane surface potential energy through its inherent electromechanical coupling characteristics (i.e., piezoelectric characteristics), thereby slowing down the development of membrane pollution through a series of electrochemical effects.

[0003] However, there are still some challenges in using the piezoelectric properties of PVDF for underwater membrane fouling control. On the one hand, the intrinsic piezoelectric coefficient of PVDF is low. 33 It is only about 33pC / N, which makes it difficult to obtain excellent output performance under low stress loads. Therefore, the existing technology usually chooses to mix inorganic dielectric particles or piezoelectric particles such as zinc oxide (ZnO) and barium titanate (BaTiO3) into the PVDF matrix to improve the overall piezoelectric performance of the mixed matrix. On the other hand, although the blended inorganic piezoelectric particles can effectively improve the piezoelectric performance of the PVDF mixed matrix in the air, it is difficult to achieve ideal results when the relevant strategies are applied to the water environment or water purification process. At present, when PVDF piezoelectric film is applied to water environment and membrane separation process, its underwater open circuit voltage is usually less than 150mV under conventional driving pressure (0.04~0.2MPa), which is only about one percent of its output voltage in the air, which seriously limits the underwater performance expression of PVDF piezoelectric film. At the same time, there is a lack of material preparation technology for improving the underwater output performance of piezoelectric materials at this stage, which further limits the application of PVDF piezoelectric materials in the fields of water treatment and membrane separation. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity, comprising the following steps:

[0007] The casting solution is prepared by using graphene oxide, organic solvent, porogen and PVDF as raw materials;

[0008] The casting solution is coated on a flat plate and scraped to form a liquid film, and then the liquid film is immersed in a pure water coagulation bath set in a negative electrode DC electric field for phase separation and synchronous polarization to obtain a PVDF porous membrane;

[0009] The PVDF porous membrane is subjected to hydrophobic modification to obtain the PVDF composite ultrafiltration membrane.

[0010] The present invention induces the formation of a polar PVDF-β phase by mixing an appropriate amount of graphene oxide (GO) into the casting solution, thereby promoting interfacial polarization at the organic-inorganic phase interface and improving the dielectric properties (i.e., polarization potential) of the casting solution; then, a negative DC electric field is applied during the phase transformation process to promote GO orientation and induce the PVDF molecular dipoles to form out-of-plane orientation, thereby improving the intrinsic piezoelectric activity of the PVDF / GO matrix; finally, the PVDF / GO porous membrane is hydrophobically modified to improve its interfacial double layer structure and interfacial ion concentration in an aqueous environment, reduce the dissipation effect of charged ions in water on the polarization charge of the piezoelectric membrane, improve its underwater piezoelectric performance expression, and finally obtain a piezoelectric separation membrane with excellent underwater piezoelectric activity and electric anti-pollution ability.

[0011] Furthermore, the diameter of the graphene oxide is 0.5-100 nm.

[0012] Further, the organic solvent includes N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or dimethylacetamide (DMAC); and / or, the porogen includes polyvinylpyrrolidone (PVP), polyethylene glycol (PEG) or lithium chloride (LiCl).

[0013] Furthermore, the casting solution comprises the following raw materials in percentage by mass: 0.1-1.5% of graphene oxide, 17-24% of PVDF, 0.5-4% of porogen, and the remainder of organic solvent.

[0014] Porogens are used to form pores during membrane preparation.

[0015] Furthermore, the graphene oxide, organic solvent, porogen and PVDF are heated and stirred to prepare the casting solution; the heating and stirring temperature is 45 to 75° C., the time is 6 to 10 hours, and the stirring speed is 300 to 500 rpm;

[0016] The thickness of the casting solution on the flat plate is 150-350 μm.

[0017] Furthermore, the degassing method is static degassing, and the static degassing time is ≥ 24h.

[0018] Furthermore, the intensity of the electric field is 200-800 V / mm, the temperature of the phase separation and synchronous polarization is 15-25° C., and the time is 5-30 min.

[0019] Furthermore, the hydrophobic modification method comprises the following steps: uniformly coating the hydrophobic modification solution on the surface of the PVDF porous membrane, and maintaining a pressure of 5 to 80 kPa during the coating process;

[0020] The ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane is 1-7 mL: 1 cm 2 ;

[0021] The hydrophobic modification solution is composed of the following raw materials in percentage by mass: 0.5-5% of long-chain silane and 95-99.5% of normal hexane.

[0022] Furthermore, the long-chain silane includes triethoxy (1H, 1H, 2H, 2H-nonafluorohexyl) silane (C 12 H 19 F9O3Si), trichloro(1H,1H,2H,2H-tridecafluorooctyl)silane(C8H4Cl3F 13 Si) or 1H,1H,2H,2H-perfluorodecyltriethoxysilane (C 16 H 19 F 17 O3Si).

[0023] The second technical solution of the present invention: a PVDF composite ultrafiltration membrane prepared by the above preparation method.

[0024] The third technical solution of the present invention: an application of the above-mentioned PVDF composite ultrafiltration membrane in water purification.

[0025] The present invention discloses the following technical effects:

[0026] (1) The present invention improves the intrinsic piezoelectric properties of the material by mixing GO into the casting solution and simultaneously applying a negative DC electric field during the phase transformation process.

[0027] (2) The present invention improves the piezoelectric output performance of the membrane material in water by performing hydrophobic modification on the membrane material.

[0028] (3) The present invention organically combines GO blending, negative electrode DC electric field polarization and hydrophobic modification to finally prepare a PVDF composite ultrafiltration membrane with significant underwater piezoelectric activity and electric anti-pollution ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 FTIR images of the PVDF composite ultrafiltration membranes prepared in Examples 1 to 6;

[0031] Figure 2 XRD diagram of the PVDF composite ultrafiltration membrane prepared in Examples 1 to 6;

[0032] Figure 3 This is a schematic diagram of a test device for underwater piezoelectric output signals;

[0033] Figure 4 Schematic diagram of the preparation process of PVDF composite ultrafiltration membrane;

[0034] Figure 5 The electrical signals of the PVDF composite ultrafiltration membranes prepared in Examples 1 to 6 (with different blended GO contents);

[0035] Figure 6 The electrical signals of the PVDF composite ultrafiltration membranes prepared in Examples 2 to 4 (Poling) and Examples 7 to 9 (nPoling);

[0036] Figure 7 The electrical signals of the PVDF composite ultrafiltration membranes prepared in Examples 2 to 4 (Hob) and Examples 10 to 12;

[0037] Figure 8 The electrical signals of the PVDF composite ultrafiltration membranes prepared in Examples 4 and 13 (with different applied electric field strengths);

[0038] Fig. 9 The electrical signals of the PVDF composite ultrafiltration membranes prepared in Examples 4 and 14 (the silane chain lengths used for hydrophobic modification are different);

[0039] Fig.10For Example 1 (Hob-PM0-Poling), Example 9 (Hob-PM 0.5 -nPoling), Example 12 (PM 0.5 -Poling), Example 4 (Hob-PM 0.5 -Poling) prepared PVDF composite ultrafiltration membrane to bovine serum albumin (BSA) fouling resistance.

[0040] Fig.11 The electrical signal of the PVDF composite ultrafiltration membrane prepared in Examples 2 and 15-16;

[0041] Fig.12 The electrical signal of the PVDF composite ultrafiltration membrane prepared in Examples 2 and 17. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0047] The “parts” described in the following examples are all “parts by weight”.

[0048] Example 1

[0049] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without mixing graphene oxide):

[0050] (1) The organic solvent NMP, the polymer PVDF and the porogen PVP were mixed in a ratio of 76wt%:20wt%:4wt% (the total mass percentage of NMP, PVDF and PVP was 100%), then heated in a water bath at 60°C, dissolved using mechanical stirring at 400 rpm for 8 h, and allowed to stand for degassing for 24 h to obtain a casting solution.

[0051] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0052] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane (denoted as PM0).

[0053] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0054] The PVDF composite ultrafiltration membrane prepared in this example was dried at 50°C for 2 h and then subjected to FTIR and XRD tests. Figure 1 and Figure 2 .

[0055] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium dual-electrode system under the action of a peristaltic pump (see the schematic diagram of the underwater piezoelectric output signal test device for details). Figure 3 ), the peristaltic pump provides a pulse pressure of 90 kPa.

[0056] After testing, when graphene oxide was not added, it was found from the FTIR graph that -1There is a non-polar crystal characteristic peak at 18.4°; from the XRD diagram, it is found that the peak of the α phase is at 18.4°, which means that when graphene oxide is not added, the membrane is highly non-polar. Combined with the measured average underwater piezoelectric output signal of the PVDF composite ultrafiltration membrane is 150mV, the result is: when graphene oxide is not added, the β phase content of PVDF is low and it has a non-polar characteristic peak, indicating that it does not have strong piezoelectric properties.

[0057] Example 2

[0058] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the amount of graphene oxide is 0.1wt%):

[0059] (1) First, 0.1 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.9 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0060] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0061] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and the pressure of 10 kPa was maintained during the coating process. The coating time was 30 min, and then the coated membrane was left to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane (denoted as PM 0.1 ).

[0062] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0063] The schematic diagram of the preparation process of PVDF composite ultrafiltration membrane is shown in Figure 4 .

[0064] The PVDF composite ultrafiltration membrane prepared in this example was dried at 50°C for 2 h and then subjected to FTIR and XRD tests. Figure 1 and Figure 2 .

[0065] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0066] After testing, after adding 0.1wt% graphene oxide, it was found from the FTIR graph at 763cm -1 The nonpolar peak at 510 cm -1 and 840cm -1 The peak value of the polarity peak at 18.4° increased. From the XRD diagram, it was found that at 18.4°, the α-phase crystal form decreased, and at 20.8°, the β-phase crystal form increased. Combined with the average piezoelectric output signal of PVDF measured to be 400mV, the result was obtained: when 0.1wt% graphene oxide was added, it was found from FTIR and XRD that the piezoelectric properties of PVDF itself were improved, indicating that the blended graphene oxide can improve the piezoelectric properties of the PVDF composite ultrafiltration membrane itself.

[0067] Example 3

[0068] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the amount of graphene oxide is 0.3wt%):

[0069] (1) First, 0.3 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.7 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0070] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0071] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and the pressure of 10 kPa was maintained during the coating process. The coating time was 30 min, and then the coated membrane was left to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane (denoted as PM0.3 ).

[0072] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0073] The PVDF composite ultrafiltration membrane prepared in this example was dried at 50°C for 2 h and then subjected to FTIR and XRD tests. Figure 1 and Figure 2 .

[0074] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0075] After testing, after adding 0.3wt% graphene oxide, it was found from the FTIR graph at 763cm -1 The nonpolar peak at 510 cm -1 and 840cm -1 The peak value of the polarity peak at 18.4° is significantly improved compared to the peak value of the membrane without graphene oxide. From the XRD diagram, it is found that at 18.4°, the α-phase crystal form decreases to almost no peak, and at 20.8°, the β-phase crystal form increases. Combined with the measured average piezoelectric output signal of PVDF of 600mV, the result is: when 0.3wt% graphene oxide is added, it is found from FTIR and XRD that the piezoelectric performance of PVDF itself is improved, indicating that the blended graphene oxide can improve the piezoelectric performance of the PVDF composite ultrafiltration membrane itself.

[0076] Example 4

[0077] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the amount of graphene oxide is 0.5wt%):

[0078] (1) First, 0.5 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.5 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0079] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0080] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and the pressure of 10 kPa was maintained during the coating process. The coating time was 30 min, and then the coated membrane was left to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane (denoted as PM 0.5 ).

[0081] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0082] The PVDF composite ultrafiltration membrane prepared in this example was dried at 50°C for 2 h and then subjected to FTIR and XRD tests. Figure 1 and Figure 2 .

[0083] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0084] After testing, after adding 0.5wt% graphene oxide, it was found from the FTIR graph at 763cm -1 The nonpolar peak at 510 cm -1 and 840cm -1 The peak value of the polarity peak at 18.4° is significantly improved compared to the peak value of the membrane without graphene oxide. From the XRD diagram, it is found that at 18.4°, the α-phase crystal disappears, and at 20.8°, the β-phase crystal increases. Combined with the measured average piezoelectric output signal of PVDF of 900mV, the result is: when 0.5wt% graphene oxide is added, it is found from FTIR and XRD that the piezoelectric performance of PVDF itself is improved, indicating that the blended graphene oxide can improve the piezoelectric performance of the PVDF composite ultrafiltration membrane itself.

[0085] Example 5

[0086] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the amount of graphene oxide is 1wt%):

[0087] (1) First, 1 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0088] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0089] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized, thereby obtaining a PVDF composite ultrafiltration membrane (denoted as PM1).

[0090] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0091] The PVDF composite ultrafiltration membrane prepared in this example was dried at 50°C for 2 h and then subjected to FTIR and XRD tests. Figure 1 and Figure 2 .

[0092] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0093] After testing, after adding 1wt% graphene oxide, it was found from the FTIR graph that -1 The nonpolar peak at 510 cm -1 and 840cm -1The peak value of the polarity peak at 18.4° is significantly improved compared to the peak value of the membrane without graphene oxide. From the XRD diagram, it is found that at 18.4°, the α phase crystal disappears, and at 20.8°, the β phase crystal increases. Combined with the average piezoelectric output signal of PVDF of 600mV, the result is: when 1wt% graphene oxide is added, it is found from FTIR and XRD that the piezoelectric performance of PVDF itself is improved, indicating that the blended graphene oxide can improve the piezoelectric performance of the PVDF composite ultrafiltration membrane itself.

[0094] Example 6

[0095] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the amount of graphene oxide is 1.5wt%):

[0096] (1) First, 1.5 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 74.5 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0097] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0098] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and the pressure of 10 kPa was maintained during the coating process. The coating time was 30 min, and then the coated membrane was left to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane (denoted as PM 1.5 ).

[0099] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0100] The PVDF composite ultrafiltration membrane prepared in this example was dried at 50°C for 2 h and then subjected to FTIR and XRD tests. Figure 1 and Figure 2 .

[0101] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0102] After testing, after adding 1.5wt% graphene oxide, it was found from the FTIR graph at 763cm -1 The nonpolar peak at 510 cm -1 and 840cm -1 The peak value of the polarity peak at 18.4° is significantly improved compared to the peak value of the membrane without graphene oxide. From the XRD diagram, it is found that at 18.4°, the α-phase crystal disappears, and at 20.8°, the β-phase crystal increases. Combined with the average piezoelectric output signal of PVDF measured to be 400mV, the result is: when 1.5wt% graphene oxide is added, it is found from FTIR and XRD that the piezoelectric performance of PVDF itself is improved, indicating that the blended graphene oxide can improve the piezoelectric performance of the PVDF composite ultrafiltration membrane itself.

[0103] Example 7

[0104] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without polarization):

[0105] (1) First, 0.1 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.9 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0106] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is directly immersed in a pure water coagulation bath. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0107] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0108] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0109] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0110] It was found through measurement that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 100 mV.

[0111] Example 8

[0112] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without polarization):

[0113] (1) First, 0.3 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.7 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0114] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is directly immersed in a pure water coagulation bath. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0115] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0116] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0117] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0118] It was found through measurement that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 130 mV.

[0119] Example 9

[0120] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without polarization):

[0121] (1) First, 0.5 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.5 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0122] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is directly immersed in a pure water coagulation bath. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0123] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0124] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0125] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0126] It was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 150 mV.

[0127] Example 10

[0128] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without hydrophobic modification):

[0129] (1) First, 0.1 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.9 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0130] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm and the time is 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF composite ultrafiltration membrane.

[0131] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0132] After testing, when 0.1wt% graphene oxide was added, coupled electric field in-situ polarization was performed, and no hydrophobic modification was performed, it was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane was 100mV in the platinum-titanium double electrode system. This shows that the electrical signal generated by the electromechanical coupling is affected by the double electric layer, resulting in its transmission in water being weakened.

[0133] Embodiment 11

[0134] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without hydrophobic modification):

[0135] (1) First, 0.3 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.7 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0136] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm and the time is 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF composite ultrafiltration membrane.

[0137] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0138] After testing, when 0.3wt% graphene oxide was added, coupled with electric field in-situ polarization, and no hydrophobic modification was performed, it was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane was 150mV under the platinum-titanium double electrode system. This shows that the electrical signal generated by the electromechanical coupling is affected by the double electric layer, resulting in its transmission in water being weakened.

[0139] Example 12

[0140] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (without hydrophobic modification):

[0141] (1) First, 0.5 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.5 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0142] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm and the time is 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF composite ultrafiltration membrane.

[0143] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0144] After testing, when 0.5wt% graphene oxide was added, coupled electric field in-situ polarization was performed, and no hydrophobic modification was performed, it was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane was 200mV in the platinum-titanium double electrode system. This shows that the electrical signal generated by the electromechanical coupling is affected by the double electric layer, resulting in its transmission in water being weakened.

[0145] Example 13

[0146] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (electric field polarization intensity 100V / mm):

[0147] (1) First, 0.5 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.5 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0148] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 100 V / mm and the time is 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0149] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0150] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0151] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0152] It was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 200 mV.

[0153] Embodiment 14

[0154] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (replacing the long-chain silane used in the hydrophobic modification solution with a short-chain silane):

[0155] (1) First, 0.5 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.5 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0156] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0157] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0158] The hydrophobic modification solution consisted of 2 wt % triethoxymethylsilane and 98 wt % n-hexane.

[0159] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0160] It was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 250 mV.

[0161] Embodiment 15

[0162] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the size of graphene oxide is 0.2nm):

[0163] (1) First, 0.1 wt% graphene oxide (GO) (diameter 0.2 nm) was dispersed in 75.9 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0164] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0165] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0166] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0167] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0168] It was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 200 mV.

[0169] Example 16

[0170] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the size of graphene oxide is 500nm):

[0171] (1) First, 0.1 wt% graphene oxide (GO) (diameter 500 nm) was dispersed in 75.9 wt% organic solvent NMP under ultrasound, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0172] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a negative DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm for 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0173] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0174] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0175] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0176] It was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 150 mV.

[0177] Embodiment 17

[0178] A method for preparing a PVDF composite ultrafiltration membrane with underwater piezoelectric activity (the polarization electric field is a positive DC electric field):

[0179] (1) First, 0.1 wt% graphene oxide (GO) (diameter 50 nm) was dispersed in 75.9 wt% organic solvent NMP under ultrasonic action, and then polymer PVDF and porogen PVP were added to the solution in a ratio of 20 wt%:4 wt% (the total mass percentage of GO, NMP, PVDF and PVP was 100%), followed by heating in a 60°C water bath, dissolving using mechanical stirring at 400 rpm for 8 h, and standing for degassing for 24 h to obtain a casting solution.

[0180] (2) The casting liquid is coated on a glass plate and made into a flat plate with a thickness of 250 μm using a wet film preparation device. The glass plate with the casting liquid is immersed in a pure water coagulation bath set in a positive DC electric field for phase separation and synchronous polarization. The electric field strength is 600 V / mm and the time is 15 min. The coagulation bath temperature is maintained at room temperature (25°C) until the casting liquid is completely gelled and the membrane is taken out to obtain a PVDF porous membrane.

[0181] (3) The hydrophobic modification solution was uniformly coated on the surface of the PVDF porous membrane (the ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane was 5 mL: 1 cm 2 ), and maintained a pressure of 10 kPa during the coating process. The coating time was 30 min, and then the coated membrane was allowed to stand at room temperature for 24 h to ensure that the n-hexane was completely volatilized to obtain a PVDF composite ultrafiltration membrane.

[0182] The hydrophobic modification solution consisted of 2 wt % triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane and 98 wt % n-hexane.

[0183] The PVDF composite ultrafiltration membrane prepared in this example was tested for underwater electrical signals using a platinum-titanium double electrode system under the action of a peristaltic pump, and the peristaltic pump provided a pulse pressure of 90 kPa.

[0184] It was found that the average piezoelectric output signal of the PVDF composite ultrafiltration membrane prepared in this example was 250 mV.

[0185] Effect Example 1

[0186] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes (Examples 1 to 6) prepared by blending different amounts of graphene oxide (GO) were measured. Figure 5 .

[0187] from Figure 5 It can be seen that with the increase of GO content, the piezoelectric signal of PVDF composite ultrafiltration membrane first increases and then decreases, reaching a maximum of 1200mV. Compared with the PVDF composite ultrafiltration membrane without graphene oxide blending, the piezoelectric output signal is increased by 5 times, which shows that the content of blended graphene oxide has a significant effect on the piezoelectric properties of PVDF piezoelectric separation membrane.

[0188] Effect Example 2

[0189] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes prepared in Example 2 (Poling-0.1wt%), Example 3 (Poling-0.3wt%), Example 4 (Poling-0.5wt%), Example 7 (nPoling-0.1wt%), Example 8 (nPoling-0.3wt%), and Example 9 (nPoling-0.5wt%) were measured. The results are shown in Figure 6 .

[0190] from Figure 6 It can be seen that on the basis of the same content of blended graphene oxide, after in situ electric field polarization, the piezoelectric signal of the membrane in water is 5 times higher than that of the membrane without in situ electric field polarization. The comparison illustrates the important role of in situ electric field polarization.

[0191] Effect Example 3

[0192] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes prepared in Example 2 (Hob-0.1wt%), Example 3 (Hob-0.3wt%), Example 4 (Hob-0.5wt%), Example 10 (0.1wt%), Example 11 (0.3wt%), and Example 12 (0.5wt%) were measured. The results are shown in Figure 7 .

[0193] from Figure 7 It can be seen that based on the same content of blended graphene oxide, after hydrophobic modification, the piezoelectric signal of the membrane in water is 5 times higher than that of the PVDF composite ultrafiltration membrane without hydrophobic modification. The key role of hydrophobic modification is illustrated by comparison.

[0194] Effect Example 4

[0195] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes prepared in Example 4 (Hob-PM0.5-Poling 600) and Example 13 (Hob-PM0.5-Poling 100) under different electric field strengths are measured. The results are shown in Figure 8 .

[0196] from Figure 8 It can be seen that, under the same other conditions, the piezoelectric signal of the PVDF composite ultrafiltration membrane prepared by applying an electric field strength of 600 V / mm in the phase inversion process is 5 times higher than that of the PVDF composite ultrafiltration membrane prepared by applying an electric field strength of 100 V / mm in water.

[0197] Effect Example 5

[0198] Determination Example 4 (Hob-C 12 H 19 F9O3Si-PM0.5-Poling) and Example 14 (Hob-C7H 18 The piezoelectric properties (electrical signal) of PVDF composite ultrafiltration membranes prepared by silanes of different chain lengths are shown in Fig. 9 .

[0199] from Fig. 9 It can be seen that under the same other conditions, the long-chain silane (triethoxy (1H, 1H, 2H, 2H-nonafluorohexyl) silane) (C 12 H 19 The PVDF composite ultrafiltration membrane prepared by using short-chain silane (triethoxymethylsilane) (C7H 18 The piezoelectric signal of the composite PVDF ultrafiltration membrane prepared by O3Si) in water is 5 times higher.

[0200] Effect Example 6

[0201] Determination of Example 1 (Hob-PM0-Poling), Example 9 (Hob-PM 0.5 -nPoling), Example 12 (PM 0.5 -Poling), Example 4 (Hob-PM 0.5 -Poling) prepared PVDF composite ultrafiltration membrane to bovine serum albumin (BSA) contamination resistance, the results are shown in Fig.10 .

[0202] Determination of the anti-fouling performance of ultrafiltration membrane (i.e., resistance to fouling by bovine serum albumin (BSA)):

[0203] At the beginning of the filtration experiment, the PVDF ultrafiltration membrane sample was placed in an ultrafiltration cup and pre-pressed with deionized water at 0.1 MPa for 60 minutes to obtain a stable initial flux recorded as J0. The filtered water was then replaced with a 20 mg / L bovine serum albumin solution and the pressure was adjusted to 0.09 MPa. Considering the different initial fluxes of different PVDF ultrafiltration membrane samples, the steady-state flux of the PVDF ultrafiltration membrane sample was tested when the permeate volume reached 500 mL and recorded as J p After that, a simple physical cleaning was performed with deionized water, and then the pure water flux of the PVDF ultrafiltration membrane sample was tested again and recorded as J c The anti-fouling performance of PVDF ultrafiltration membrane can be measured by the total fouling resistance (R t ), irreversible pollution resistance (R i ) and reversible pollution resistance (R r), the total pollution resistance refers to the ratio of water flux loss after pollution to pure water flux, calculated according to formula (1); the reversible pollution resistance refers to the ratio of the partial flux recovered by simple physical cleaning to the pure water flux before pollution, calculated according to formula (2); the irreversible pollution resistance refers to the ratio of the partial flux that is still difficult to recover after physical cleaning to the pure water flux before pollution, calculated according to formula (3).

[0204]

[0205]

[0206]

[0207] from Fig.10 It can be seen that, on the basis of other conditions being the same, the total pollution resistance of PVDF composite ultrafiltration membrane with GO added to BSA is reduced by more than 3 times compared with that of PVDF composite ultrafiltration membrane without GO added, the total pollution resistance of PVDF composite ultrafiltration membrane with electric field polarization is reduced by more than 3 times compared with that of PVDF composite ultrafiltration membrane without electric field polarization, and the total pollution resistance of PVDF composite ultrafiltration membrane with hydrophobic modification is reduced by 4 times compared with that of PVDF composite ultrafiltration membrane without hydrophobic modification. Among them, the irreversible resistance of PVDF composite ultrafiltration membrane prepared by blending graphene oxide, in-situ electric field polarization and hydrophobic modification to BSA is reduced to 0.05, and its anti-pollution performance is significantly improved.

[0208] Effect Example 7

[0209] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes prepared using graphene oxide of different diameters in Example 2 (GO-50nm) and Example 15 (GO-0.2nm) were measured. The results are shown in Fig.11 .

[0210] from Fig.11 It can be seen that, under the same other conditions, the piezoelectric signal of the PVDF composite ultrafiltration membrane prepared using graphene oxide with a diameter of 50 nm is 1 times higher than that of the composite PVDF ultrafiltration membrane prepared using graphene oxide with a diameter of 0.2 nm in water.

[0211] Effect Example 8

[0212] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes prepared using graphene oxide of different diameters in Example 2 (GO-50nm) and Example 16 (GO-500nm) were measured. The results are shown in Fig.11 .

[0213] from Fig.11It can be seen that, under the same other conditions, the piezoelectric signal of the PVDF composite ultrafiltration membrane prepared using graphene oxide with a diameter of 50 nm is 1 times higher than that of the composite PVDF ultrafiltration membrane prepared using graphene oxide with a diameter of 500 nm in water.

[0214] Effect Example 9

[0215] The piezoelectric properties (electrical signals) of the PVDF composite ultrafiltration membranes prepared by polarization electric fields of different electrical properties in Example 2 (negative DC electric field polarization) and Example 17 (positive DC electric field polarization) are measured. The results are shown in Fig.12 .

[0216] from Fig.12 It can be seen that, under the same other conditions, the piezoelectric signal of the PVDF composite ultrafiltration membrane prepared by negative DC electric field polarization in water is 1 times higher than that of the composite PVDF ultrafiltration membrane prepared by positive DC electric field polarization.

[0217] The comparison shows that the blended graphene oxide, in-situ electric field polarization and hydrophobic modification play a synergistic role in improving the piezoelectric properties of the membrane and achieving anti-pollution effects.

[0218] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a PVDF composite ultrafiltration membrane having underwater piezoelectric activity, characterized in that: The following steps are involved: The casting solution is prepared by using graphene oxide, organic solvent, porogen and PVDF as raw materials; The casting solution is coated on a flat plate, and then immersed in a pure water coagulation bath set in a negative electrode DC electric field for phase separation and synchronous polarization to obtain a PVDF porous membrane; The PVDF porous membrane is subjected to hydrophobic modification to obtain the PVDF composite ultrafiltration membrane.

2. The preparation method according to claim 1, characterized in that: The diameter of the graphene oxide is 0.5-100 nm.

3. The preparation method according to claim 1, characterized in that: The organic solvent includes N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide or dimethylacetamide; and / or the porogen includes polyvinylpyrrolidone, polyethylene glycol or lithium chloride.

4. The preparation method according to claim 1, characterized in that: The casting solution comprises the following raw materials in percentage by mass: 0.1-1.5% of graphene oxide, 17-24% of PVDF, 0.5-4% of porogen, and the remainder of organic solvent.

5. The preparation method according to claim 1, characterized in that: The graphene oxide, organic solvent, porogen and PVDF are heated and stirred to prepare the casting solution; the heating and stirring temperature is 45 to 75° C.; The thickness of the casting solution on the flat plate is 150-350 μm.

6. The preparation method according to claim 1, characterized in that: The intensity of the electric field is 200-800 V / mm, and the time of the phase separation and synchronous polarization is 5-30 minutes.

7. The preparation method according to claim 1, characterized in that: The hydrophobic modification method comprises the following steps: uniformly coating the hydrophobic modification solution on the surface of the PVDF porous membrane, and maintaining a pressure of 5 to 80 kPa during the coating process; The ratio of the amount of the hydrophobic modification solution to the area of ​​the PVDF porous membrane is 1-7 mL: 1 cm 2 ; The hydrophobic modification solution is composed of the following raw materials in percentage by mass: 0.5-5% of long-chain silane and 95-99.5% of normal hexane.

8. The preparation method according to claim 7, characterized in that: The long-chain silane includes triethoxy (1H, 1H, 2H, 2H-nonafluorohexyl) silane, trichloro (1H, 1H, 2H, 2H-tridecafluorooctyl) silane or 1H, 1H, 2H, 2H-perfluorodecyl triethoxy silane.

9. A PVDF composite ultrafiltration membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the PVDF composite ultrafiltration membrane according to claim 9 in water purification.

Citation Information

Patent Citations

  • Preparation method of PVDF / modified reduced graphene oxide composite film, composite film and sensor

    CN111098534A

  • Casting preparation process of ultra-thin PVDF (polyvinylidene fluoride) piezoelectric film

    CN115340691A

  • PVDF piezoelectric film and preparation method thereof

    CN115612145A

  • Preparation method of PVDF beta crystal piezoelectric ultrafiltration membrane

    CN117046325A

Cited By

  • Preparation method and application of PVDF-based hollow fiber nanofiltration membrane with piezoelectric responsiveness

    CN120115022A

  • A method for preparing and applying a piezoelectrically responsive PVDF-based hollow fiber nanofiltration membrane.

    CN120115022B